Reviews on the Effect of Single Point Incremental Forming (SPIF) Process Parameters on Surface Roughness of Aluminum Alloy AA1050-H14 Sheet Metal - Phan, Nhat Tuan; Dinh, Le Cao Ky; Nguyen, Thanh Vu; Vo, Tuyen (Applied mechanics and materials, 2023)
Incremental Sheet Forming (ISF) is emerging as one of the popular dieless forming processes for the small-sized batch production of sheet metal components. However, the parts formed by the ISF process suffer from poor surface finish, geometric inaccuracy, and non-uniform thinning, which leads to poor part characteristics. This paper deals with the influence of single point continuous local forming process parameters on the surface roughness of the product. Design of trials used for research planning and analysis and interpretation of results. The results indicate that the tool diameter (D), vertical step-down size (Δz), and sheet thickness (t) have significant effects on the produced profile accuracy, while the feed rate (f) is not significant. As a general rule, thin sheets with greater tool diameters yielded the best surface quality. The results also show that controlling all surface quality features is complex because of the contradicting effects of, and interactions between, a number of the process parameters.